Pottery Production in Egypt: the chaîne opératoire as a Heuristic Tool (Studies in Ancient Art and Civilisation, 2017)
The main steps in the production of pottery are well known and are often similar across much of the world. However, the loci of production where such steps took place, namely the workshops/workspaces, have traditionally attracted less attention from Egyptologists than have the major religious and funerary monuments. In the past three decades or so, however, there has been an increased emphasis on settlement archaeology and ‘daily life’ and this shift has increased the importance of understanding production loci.This paper attempts to use the concept of the chaîne opératoire in association with spatial information in the way which Monteix (2016) has done in his study of Pompeian bakeries in an attempt to better understand the layout of workshops and to identify potential gaps in the archaeological record.